Rancang Bangun Sistem Informasi Pengelolaan Uang Sekolah di SMK Plus Bani Muchtar Rancaekek - Lilis Diana; Encep Supriatna; Ovi Siti Roviah Alawiah (Jurnal Dimamu, 2022)
In research conducted in the process of managing school finances at SMK Plus Bani Muchtar Rancaekek it still runs manually so that there are still many errors in the transaction process and in making reports. The purpose of writing this final project is to change the financial management information system at SMK Bani Muchtar Rancaekek from a manual system to a computerized system using Microsoft Visual Foxpro 9.0. This final project was made based on a descriptive method approach in collecting information data needed to make a picture of a situation, event, or trend that is developing. As for the system design using SDLC (System Development Life Cycle) with the waterfall model. Using design toos in the form of DFD, Structurt Chart, Flowmap and ER Diagrams.The system was created using Microsoft Visual Foxpro 9.0 and Foxpro database. With the design of the system made, it is expected to make it easier for employees in the Administration section and minimize errors that often occur in school payment transactions and also errors that occur in making financial management reports at schools.